Geo-environmental site characterization in a sanitary landfill using Geo-electrical and geotechnical in situ techniques - Elis, Vagner R.; Zuquette, Lázaro V.; Giacheti, Heraldo L. [UNESP]; Pejon, Osni J. (My University, 2018)
In recent years there has been a steady increase in geo-environmental engineering projects requiring enhancement in the site characterization techniques. This paper presents results of a site characterization program carried out in a deactivated sanitary landfill in Brazil. The program included traditional drilling, sampling and laboratory tests and electrical resistivity tests. The advantage of using geophysical methods for guiding the use of the geotechnical in situ testing is discussed. Moreover, the necessity of additional research to adjust modern technologies for using in site characterization of tropical soils is commented.